2016
DOI: 10.15640/jisc.v4n2a11
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Universiti Sains Malaysia Muslim Staff on Factors Influencing their Intention to Perform Cash Waqf

Abstract: Starting from 2016, the Malaysia Government has reduced the budget for Public

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
2
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 15 publications
4
15
2
8
Order By: Relevance
“…Trust on BMT affects the intention to give cash waqfs at BMT. These results support previous research that trust is one of the factors that influence the intention to give cash waqf in waqf institutions (Johari et al, 2015;Mokthar, 2016). This study provides empirical evidence of the influence of trust on the intention to give cash waqf in BMT.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Trust on BMT affects the intention to give cash waqfs at BMT. These results support previous research that trust is one of the factors that influence the intention to give cash waqf in waqf institutions (Johari et al, 2015;Mokthar, 2016). This study provides empirical evidence of the influence of trust on the intention to give cash waqf in BMT.…”
Section: Discussionsupporting
confidence: 90%
“…This behavior certainly applies to nonbusiness organizations, such as endowments. Several studies at waqf institutions have revealed that perception (Mokthar, 2016), trust (Johari et al, 2015;Osman et al, 2015), behavior, and subjective norms (Musa & Salleh, 2018) can influence intentions to give endowments. Based on the discussion, thus the following hypotheses are proposed.…”
Section: Relation Among Transparency Accountability and Trustmentioning
confidence: 99%
See 2 more Smart Citations
“…Studi lain menunjukan bahwa religusitas merupakan faktor utama yang memengaruhi seseorang untuk berwakaf uang (Mokthar, 2016), bahkan dapat membuat seseorang berkontribusi kembali dalam melakukan wakaf uang (Johari et al, 2015). Religiusitas juga memengaruhi perilaku Muslim untuk berpartisipasi dalam wakaf uang (Shukor et al, 2017).…”
Section: Religiusitasunclassified